2009
DOI: 10.2489/jswc.64.4.253
|View full text |Cite
|
Sign up to set email alerts
|

STEEP: Impact of long-term conservation farming research and education in Pacific Northwest wheatlands

Abstract: Erosion took a serious toll of prime topsoil from wheat fields in the Pacific Northwest United States since farming began in the 1870s. By the mid-1900s, it had become a serious environmental and economic threat to the region that produces world-record rainfed grain yields and almost 13% of the US wheat crop. Of significance is that 80% of the nation's specialty soft white wheat is grown here for food grain, of which 90% is exported. To combat the severe erosion, wheat growers, the experiment stations, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Instead, farmers will continue to rely on tillage which contributes to problems such as soil erosion, degradation of soil quality, high carbon footprint and yield reduction in the long run [48][49][50][51][52].…”
mentioning
confidence: 99%
“…Instead, farmers will continue to rely on tillage which contributes to problems such as soil erosion, degradation of soil quality, high carbon footprint and yield reduction in the long run [48][49][50][51][52].…”
mentioning
confidence: 99%
“…These data on soil water use by WP agree closely with those reported by Miller and Holmes (2012) in Montana and Merrill et al (2004) in North Dakota. However, by late March, WP plots had only 13 mm more soil water than WW plots (Table 2) because: (i) the greater the surface residue cover, the more water will be stored in the soil (e.g., WP produces little residue compared to WW); and (ii) the drier the soil, the more overwinter precipitation will be stored in the soil (Kok et al, 2009). …”
Section: Soil Watermentioning
confidence: 99%
“…The projects fostered collaborations among researchers, farmers, crop advisors and agribusinesses. Significant gains in conservation farming were documented, but adoption was not universal (Kok et al, 2009). …”
Section: Datementioning
confidence: 99%
“…In the iPNW, conservation tillage has reduced soil erosion and sediment loads (Kok et al, 2009;Brooks et al, 2010;Williams et al, 2014). Brown and Huggins (2012) reviewed 131 data sets from the iPNW and found that 75% of native ecosystems converted to agriculture lost at least 0.14-0.70 Mg C ha-1 year −1 and that the conversion from conventional tillage to no-till practices was predicted to increase SOC from 0.12 to 0.21 Mg C ha −1 year −1 for 75% of situations.…”
Section: Reduced Tillage and Crop Residue Managementmentioning
confidence: 99%
See 1 more Smart Citation